Identification of flavour in fresh feijoa fruit - Nyström, Angelica (SLU/Dept. of Food Science, 2013)
The aim of this study was to extract and identify volatile flavour components from peel, flesh and seeds of feijoa fruit separately and further determine its flavour profile. Obtained information is aimed to be used to develop a new flavour mixture for the food industry. The volatile flavour fraction of feijoa fruit flesh, seeds and skin were isolated by ethanol extraction and steam distillation. Further an organoleptic evaluation was carried out to distinguish flavour differences within the obtained distillates to decrease the number of samples to be analysed by gas chromatography and gas chromatography-mass spectrometry. Gas chromatography analysis resulted in 13 identified flavour compounds of the 23 reference compounds used. Results showed gas chromatography-mass spectrometry to be most successful and this technique presented a great amount of data of which seven compounds are reported for the first time as flavour compounds of feijoa fruit; citronellyl acetate, cis-rose oxide, geraniol acetate, isoamyl acetate, ethyl octanoate, D-limonene and humulane-1,6-dien-3-ol. Further analysis is needed to evaluate the extent of unique findings of flavour compounds and to evaluate how they contribute to the flavour of feijoa fruit to be able to produce a flavour mixture for the food industry.